2021
DOI: 10.3390/microorganisms9010199
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplant from Human to Mice Gives Insights into the Role of the Gut Microbiota in Non-Alcoholic Fatty Liver Disease (NAFLD)

Abstract: Non-alcoholic fatty liver diseases (NAFLD) are associated with changes in the composition and metabolic activities of the gut microbiota. However, the causal role played by the gut microbiota in individual susceptibility to NAFLD and particularly at its early stage is still unclear. In this context, we transplanted the microbiota from a patient with fatty liver (NAFL) and from a healthy individual to two groups of mice. We first showed that the microbiota composition in recipient mice resembled the microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 81 publications
1
32
2
Order By: Relevance
“…Following these premises, translational studies were conducted, with particular regard to NAFLD disease. In one study the intestinal microbiota collected from obese donors before and after weight loss was transplanted into GF mice: Mice that received intestinal microbiota before weight loss had higher triglycerides and cholesterol liver levels than mice that received intestinal microbiota after weight loss [180]. Moreover, donor fecal microbiota transplantation studies performed in human subjects confirmed that the gut dysbiosis can per se cause hepatic steatosis mainly by means of weight gain, insulin resistance, and increased OS [67,181,182].…”
Section: Role Of Microbiota In Hepatic Steatosis and Oxidative Stressmentioning
confidence: 99%
“…Following these premises, translational studies were conducted, with particular regard to NAFLD disease. In one study the intestinal microbiota collected from obese donors before and after weight loss was transplanted into GF mice: Mice that received intestinal microbiota before weight loss had higher triglycerides and cholesterol liver levels than mice that received intestinal microbiota after weight loss [180]. Moreover, donor fecal microbiota transplantation studies performed in human subjects confirmed that the gut dysbiosis can per se cause hepatic steatosis mainly by means of weight gain, insulin resistance, and increased OS [67,181,182].…”
Section: Role Of Microbiota In Hepatic Steatosis and Oxidative Stressmentioning
confidence: 99%
“…Human and animal studies demonstrated a potential causal role of the gut microbiota in NAFLD. Mice received human NAFL microbiota and were subsequently fed a high-fructose, high-fat diet, leading them to gain more weight and have a higher number of liver triglycerides than that of mice that received healthy human microbiota [ 11 ]. The abundance of Ruminococcaceae and Tannerellaceae was increased, and the abundance of Desulfovibrionaceae and Rikenellaceae was decreased in the mice receiving human NAFL microbiota [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mice received human NAFL microbiota and were subsequently fed a high-fructose, high-fat diet, leading them to gain more weight and have a higher number of liver triglycerides than that of mice that received healthy human microbiota [ 11 ]. The abundance of Ruminococcaceae and Tannerellaceae was increased, and the abundance of Desulfovibrionaceae and Rikenellaceae was decreased in the mice receiving human NAFL microbiota [ 11 ]. Fei and colleagues reported that liver inflammation was dependent upon endotoxin expression in HFD-fed NAFLD mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysbiosis also impacts energy harvest from the diet and alters the hepatic expression of genes involved in de novo lipogenesis. Altogether, these microbiota-associated mechanisms may influence steatosis development and fecal microbiota transplants recently confirmed that the gut bacteria affect hepatic lipid accretion (8).…”
mentioning
confidence: 85%